THE EFFECT OF THE POWER OF TWO AND FOUR METHOD ON STUDENTS' LEARNING ACTIVITY IN NATURAL AND SOCIAL SCIENCES SUBJECT AT CLASS IV OF PUBLIC ELEMENTARY SCHOOL IN TEMBILAHAN HULU - Siti Marlena; Martina Napratilora (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The learning process in elementary schools often faces challenges related to conventional teaching methods that center on the teacher, resulting in low student learning activity. This study aims to determine the significant effect of applying The Power of Two and Four learning method on students' learning activity in the Natural and Social Sciences (IPAS) subject in class IV at SDN 008 Tembilahan Hulu. A quantitative approach was employed using a Quasi-Experimental design with a Nonequivalent Group Posttest Only Design. The research sample comprised 52 students, consisting of 28 students in the experimental group (Class IV.A) and 24 students in the control group (Class IV.B) selected through random sampling. Data collection instruments included questionnaires, observation sheets, and documentation. Data analysis was performed using descriptive statistics and inferential parametric statistics via the Independent Sample t-test. The results revealed that teacher observation reached 74% (good category) and student observation reached 75.79% (good category). The learning activity percentage in the experimental group reached 85.5% (very good category), whereas the control group scored 74.3% (good category). Statistical analysis produced tcount = 3.22 > ttable = 1.67591 at a significance level of 0.05. Consequently, Ha was accepted and H0 was rejected, proving that The Power of Two and Four method significantly enhances student learning activity in elementary science learning.